2015
DOI: 10.1590/2237-6089-2014-0008
|View full text |Cite
|
Sign up to set email alerts
|

Translation and cross-cultural adaptation of the Brazilian Portuguese version of the Driving Anger Scale (DAS): long form and short form

Abstract: Introduction: Driving anger has attracted the attention of researchers in recent years because it may induce individuals to drive aggressively or adopt risk behaviors. The Driving Anger Scale (DAS) was designed to evaluate the propensity of drivers to become angry or aggressive while driving. This study describes the cross-cultural adaptation of a Brazilian version of the short form and the long form of the DAS. Methods: Translation and adaptation were made in four steps: two translations and two back-translat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Cross-cultural adaptation is a fundamental step when translating a scale. 10,11 The Emotional Memory Scale designed by Strange et al had already been translated and adapted to German and has been used in important studies about cognition. 2 The Brazilian version of the Emotional Memory Scale may significantly contribute to this field of study.…”
Section: Resultsmentioning
confidence: 99%
“…Cross-cultural adaptation is a fundamental step when translating a scale. 10,11 The Emotional Memory Scale designed by Strange et al had already been translated and adapted to German and has been used in important studies about cognition. 2 The Brazilian version of the Emotional Memory Scale may significantly contribute to this field of study.…”
Section: Resultsmentioning
confidence: 99%
“…The concept of forward models with efference copies in conjunction with neural control has been suggested since the mid-twentieth century (Holst and Mittelstaedt, 1950 ; Held, 1961 ) and increasingly employed for biological investigations (Webb, 2004 ). This is because it can explain mechanisms which biological systems use to predict the consequence of their action based on sensory information, resulting in adaptive and robust behaviors in a closed-loop scenario.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, Deffenbacher et al established traffic-related scenarios to induce driving anger and developed the Driving Anger Scale (DAS), which is an effective measurement tool using cluster analysis that has established the foundation for subsequent studies [ 5 ]. Since the development of the original DAS, Britain, New Zealand, Spain and other countries have revised partial items and factor structures of the Driving Anger Scale (DAS) based on national and cultural differences and used the revised scales to conduct subsequent related studies [ 11 16 ]. In China, a study identified differences in the perception of driving anger between Chinese and German drivers.…”
Section: Introductionmentioning
confidence: 99%